Exploring nonstandard service frontline situations - Liska, Fanny; Veres, Zoltan (Marketing & Menedzsment, 2023)
THE AIMS OF THE PAPER Jaycustomer behavior often increases the unpredictability of the service to an unmanageable extent. A co-creation based development can be presumed in the attitude of the consumer and of the frontline staff. The primary goal of this research was to investigate the dynamics of interactions between customers and frontline staff, particularly in nonstandard situations. This study aimed to understand how 'jaycustomer' behavior, which includes unpredictable and challenging customer actions, impacts these interactions and the overall service process. METHODOLOGY To explore the above, the study employed a quasi-secondary data collection method (narratives, netnography). Frontline conflicts were simulated based on a mystery shopping scenario. Mystery shoppers were instructed to combine two theoretical jaycustomer types – the Belligerent and the Egocentric Edgar (the selfish) – in their approach. These shoppers were tasked with observing various aspects of frontline staff behavior, including reactions, communication, gestures, and problem-solving intentions. MOST IMPORTANT RESULTS The simulations led to the identification of distinct behavioral patterns on both sides of the customer-staff interaction. The study highlighted specific jaycustomer oriented patterns and the frontline staff's response strategies. Furthermore, essential human resource management skills in dealing with such jaycustomer scenarios were identified, providing insights into both customer and employee behavior in challenging service situations. RECOMMENDATIONS The findings of this research offer significant implications for service management and marketing theory, particularly in developing a consensual model for managing frontline processes. Additionally, the study suggests that reviewing and aligning staff training content with these research findings could be a fruitful direction for enhancing human resource management practices in customer service environments. An expert interview conducted post-experiment further affirmed special tasks for frontline management to handle such jaycustomer situations effectively.